Acceptance of aquaculture as compared with traditional fishing in the province of Cadiz (Spain): an empirical study from the standpoint of social carrying capacity - Jose Ruiz‐Chico; José Maria Biedma‐Ferrer; Antonio Rafael Peña‐Sánchez; Mercedes Jiménez‐García (Reviews in Aquaculture, 2020)
This paper analyses the acceptance of aquaculture compared with fisheries in the province of Cadiz (Spain), in the context of social carrying capacity, the point at which its presence begins to be excessive and leads to significant problems for society. Researchers conducted 558 face‐to‐face surveys to study the societal acceptance of this sector in several dimensions (social, economy, quality, environment, etc.). We have also built an index to measure this acceptance, based on the variables studied to delve into this concept. For this purpose, we have followed a principal component analysis methodology with Varimax rotation, to which we have applied the Dalenius–Hodges stratification procedure. Analysis shows a high level of acceptance for aquaculture, indicating that it is far from its social saturation point. Rather, data indicate that even further development of this activity is advisable. In addition, respondents showed some indifference between socioeconomic and environmental objectives. We can conclude that the general perception of aquaculture is better among men than women, who have greater preferences for traditional fishing, and among higher‐income consumers. Informative campaigns should be organized to target the less convinced consumers, in the context of social carrying capacity. Production systems should be adjusted to improve the existing perception that aquaculture products are less natural; this perception arises from the misuse of chemicals and feeds, factors that are believed to have adverse effects on quality and flavour.